2021
DOI: 10.31083/j.jin2003078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathophysiological mechanisms of ischemia/reperfusion injuries after recanalization therapy for acute ischemic stroke

Abstract: With the larger variety of methods employed, recanalization therapy is increasingly used to treat acute ischemic stroke resulting in about one-third of patients undergoing early neurological deterioration, in which ischemia/reperfusion injuries are the main cause, leading to increases in the infarcted area, the no-reflow phenomenon, or hemorrhagic transformation. Efficient prevention or treatment of these injuries depends on extensive knowledge of the involved mechanisms. These pathways have dual, damaging, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 225 publications
(272 reference statements)
0
22
0
Order By: Relevance
“…The acute oxygen and glucose deprivation also increases the production of reactive oxygen species (ROS) by cytosolic enzymes and mainly by mitochondria [ 9 ], with increased oxidative stress which self-propagates and induces the expression of genes encoding subunits of the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) and kainite glutamate receptors. The consequence of this upregulated gene expression is excitotoxicity, with increases in intracellular calcium concentrations in neurons and to a lesser extent in astrocytes, leading to mitochondrial dysfunction and the initiation of apoptosis [ 24 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute oxygen and glucose deprivation also increases the production of reactive oxygen species (ROS) by cytosolic enzymes and mainly by mitochondria [ 9 ], with increased oxidative stress which self-propagates and induces the expression of genes encoding subunits of the α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) and kainite glutamate receptors. The consequence of this upregulated gene expression is excitotoxicity, with increases in intracellular calcium concentrations in neurons and to a lesser extent in astrocytes, leading to mitochondrial dysfunction and the initiation of apoptosis [ 24 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…The treatment of ischemic stroke relies increasingly on recanalization strategies, with continuously expanding therapeutic time windows [ 5 , 6 , 7 , 8 ]. Unfortunately, reestablishing blood flow in a tissue previously subject to ischemia boosts oxidative stress [ 9 ] and leads to the increased release of pro-inflammatory cytokines [ 10 ], which trigger a series of pathological cascades which will directly or indirectly cause apoptosis, disruption of the blood–brain barrier (BBB), cerebral edema, and hemorrhagic transformation. Research has shown that neuroinflammatory mechanisms, intimately linked to oxidative stress, significantly contribute to neuronal injury in the acute phase of cerebral ischemia [ 11 ], ultimately increasing the magnitude of cerebral damage and neurological deficit [ 12 , 13 ] through ischemia/reperfusion (I/R) injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory response is one of the most important mechanisms involved in the process of CIRI ( 20 ). As shown in Figure 5 , levels of TNF-α in the I/R group (40.22±2.57) were significantly increased compared to the Sham group (8.55±0.98).…”
Section: Resultsmentioning
confidence: 99%
“…However, the recovery of blood flow is often accompanied by the occurrence of CIRI, which can further exacerbate the cerebral damage. To date, multiple mechanisms have been suggested to be involved in the process of CIRI, including the inflammatory response, oxidative stress, calcium overload, cell autophagy, and others ( 20 ). Numerous drugs have been used for the treatment of CIRI, including certain necroptosis inhibitors, free radical scavengers, and NMDAR antagonists, but some of them have not been approved for clinical application or exhibit poor clinical efficacy ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The subcellular localization of NMDARs plays also a critical role in the downstream signaling cascades. The activation of synaptic NMDARs triggers the expression of a variety of anti-apoptotic and pro-survival proteins via phosphorylation of cyclic-AMP responsive element-binding protein (CREB), while the activation of extrasynaptic NMDARs is followed by cellular and mitochondrial calcium overload, increased oxidative stress, dephosphorylation and inactivation of CREB, and promotion of pro-death gene expression [ 129 , 130 ]. In HD, increased calpain activity leads to activation of calcineurin, which dephosphorylates the striatal enriched tyrosine phosphatase (STEP), an enzyme able to dephosphorylate the tyrosine 1472 residue of the GluN2B subunit, leading to reduced synaptic NMDAR expression and lateral diffusion of the GluN2B-containing receptors to extrasynaptic sites [ 23 , 127 , 131 , 132 , 133 ].…”
Section: Mechanisms Of Neurodegeneration In Huntington’s Diseasementioning
confidence: 99%